Comparative genomic analysis of esophageal adenocarcinoma and squamous cell carcinoma - Agrawal, Nishant (2012)
Esophageal cancer (EC) ranks sixth in cancer death. To explore its genetic origins, we performed exomic sequencing on 11 adenocarcinomas (EAC) and 12 squamous cell carcinomas (ESCCs) from the United States. Interestingly, inactivating mutations of NOTCH1 were identified in 21% of ESCCs but not in EACs. There was a substantial disparity in the spectrum of mutations, with more indels in ESCCs, A:T>C:G transversions in EACs, and C:G>G:C transversions in ESCCs (p<0.0001). Notably, NOTCH1 mutations were more frequent in North American ESCCs (11 of 53 cases) than in ESCCs from China (1 of 48 cases). A parallel analysis found that most mutations in EACs were already present in matched Barrett’s esophagus (BE). These discoveries highlight key genetic differences between EAC and ESCC, American and Chinese ESCC, and suggest that NOTCH1 is a tumor suppressor gene in the esophagus. Finally, we provide a genetic basis for the evolution of EACs from BE.